2018
DOI: 10.1097/pai.0000000000000402
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Profiles of Endometrioid Endometrial Carcinomas With and Without Metastatic Disease

Abstract: A minority of endometrial carcinomas present at an advanced stage with a poor prognosis, and should be identified to individualize treatment. Immunohistochemical markers have been studied, but most have not been directly linked to metastasis. This study analyzes the immunohistochemical profile of endometrioid endometrial carcinomas (EECs) with and without metastases, and corresponding metastases. Tissue microarray slides from stage I EECs, stage III-IV EECs, and corresponding metastases were stained and scored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
2
8
1
Order By: Relevance
“…The percentage of L1CAM+ cases was slightly lower in our study compared with other studies [16,19,20,23,24]. This might be related to the fact that pre-operative analysis was used instead of final tumor sections in which L1CAM can be expressed focally and/or at the invasive front predominantly [25]. Our results are in line with a study reporting that patients with L1CAM+ had significantly reduced survival also in the ESMO-ESGO-ESTRO 'high and advanced/metastatic' risk group compared with normal L1CAM expression [24].…”
Section: Discussioncontrasting
confidence: 76%
“…The percentage of L1CAM+ cases was slightly lower in our study compared with other studies [16,19,20,23,24]. This might be related to the fact that pre-operative analysis was used instead of final tumor sections in which L1CAM can be expressed focally and/or at the invasive front predominantly [25]. Our results are in line with a study reporting that patients with L1CAM+ had significantly reduced survival also in the ESMO-ESGO-ESTRO 'high and advanced/metastatic' risk group compared with normal L1CAM expression [24].…”
Section: Discussioncontrasting
confidence: 76%
“…29 Interestingly, the expression of PR was shown to be lower in metastatic endometrial carcinoma lesions compared with the corresponding primary tumor, which suggests that loss of PR plays a role in EMT. 24,30 Expression of L1CAM has also been related to both distant spread and EMT, and these associations have been previously described, including in our previous paper on L1CAM. 14,15,31Y34 These studies show that expression of L1CAM is especially dependent on TGFA signaling and Wnt/A-catenin activity, both of which are inhibited by progesterone.…”
Section: Combined Value Of Er Pr and L1cam Expressionsupporting
confidence: 62%
“…The most frequently mutated genes included PTEN , ARID1A and PIK3CA . This is in line with previously reported frequencies between 37 and 61% for PTEN , 23 and 40% for ARID1A and 24 and 39% for PIK3CA in EC . POLE and TP53 were mutated in 12 and 31% of all cases.…”
Section: Discussionsupporting
confidence: 93%
“…This is in line with previously reported frequencies between 37 and 61% for PTEN, 23 and 40% for ARID1A and 24 and 39% for PIK3CA in EC. [22][23][24][25][26][27][28][29][30][31][32] POLE and TP53 were mutated in 12 and 31% of all cases. Earlier studies found similar frequencies for POLE (7-9.3%), and slightly lower rates of TP53-mutations (12.2-18%).…”
Section: Discussionmentioning
confidence: 99%